From the Cult of Chivalry to the Cult of Personality: The Seventh-century Transformation in Pallava Statecraft. (August 2017) - Devadevan, Manu V.
Between the fourth and sixth centuriesce, Pallava statecraft in South India revolved largely around the practice of making land grants to brāhmaṇa beneficiaries. These activities were concentrated in the rural agrarian belts of coastal Andhra and parts of Karnataka. The image of the king in these grants was stereotypical: a chivalrous ruler, wedded to the ideals of valour, protecting his people and swearing devotion towards his father and god. These were ideals that might have appealed to the imagination of a rural world in an agrarian milieu. However, in the early seventh centuryce, when South Asia witnessed a 'third phase of urbanization', the Pallavas turned towards Tamil Nadu, where a powerful class of peasant proprietors, the nātṭṭār, existed. In this changed historical setting, the Pallavas moved away in a significant manner from the practice of awarding land grant and making interventions into the production relations and other regimes of agrarian control. Instead, they turned towards the creation of a refined urban aesthetic infrastructure centring on the cult of the royal personality. This involved the propagation of newer images of the king, extending patronage to literary practices, drama and music, and building temples for āgamic deities such as Śiva and Viṣṇu on a scale large enough to promote ingenious forms of architecture and iconography. This new aesthetic infrastructure was widely influential, eventually spread to other parts of the subcontinent, transforming the practice of statecraft in South Asia.